PENGEMBANGAN PETERNAKAN BERSIH DI DESA NGUNUT KECAMATAN JUMANTONO KABUPATEN KARANGANYAR - Chusniatun, Chusniatun; Priyono, Kuswaji Dwi; Harismah, Kun; Suharjo, Suharjo; Muhtadi, Muhtadi; Putro, Sartono (WARTA, 2015)
In the Pemitra community service activities for development cleaner farming in Desa Ngunut Kecamatan Jumantono kabupaten Karanganyar, has been done for directing activities, training, and mentoring for farmers of cattle and chickens in Desa Ngunut, Jumantono, Karanganyar. In this Pemitra activities have been conductedbriefings and training on producing of liquid and solid organic fertilizer, planting cassava  and  sengon  by  utilizing  manure,  the  introduction  of  biogas  technology applications on cattle ranchers. The results that have been obtained from this Pemitra community activities that partners have been able to understand and have the skills for managing livestock clean the biogas technology applications, the use of probiotics or fermentator in farm management, made of solid and liquid organic fertilizer, as well as the use of organic fertilizer for agricultural development cassava and sengon. The constraints and problems had been faced by the partners were 1) lack of farmer groups  that have  organizational unity  in designing,  managing, implementing  and evaluating the work program. So that the unity and continuity in performing community service activities can not be done well, 2) Most of the participants were active inpemitra was the village officials and their family, so not much give a breadth of benefits to the general public.